Kontribusi Pola Asuh Orang Tua Demokratis terhadap Perilaku Sosial Anak Generasi Z - Ignasia Sekar Kinasih; Gendon Barus (Jurnal Kajian dan Penelitian Umum, 2024)
This research aims to 1) find out how high democratic parenting patterns are in generation Z children, 2) identify low levels of democratic parenting pattern scale items, 3) find out how high (good) the social behavior of generation Z children is, 4) Identify Which items on the Generation Z social behavior scale have identified low scores, 5) Find out whether democratic parenting patterns contribute to the social behavior of Generation Z children.This research uses associative quantitative methods. The subjects of this research were 85 students at SMA Stella Duce 2 Yogyakarta who belonged to generation Z. Using two scales, the Parenting Patterns scale (44 valid items with a Cronbach's alpha reliability value of 0.927) and the Social Behavior scale (29 valid items with a Cronbach's alpha reliability value alpha of 0.927). Data collection using Google Form. Using descriptive tests, normality tests, linearity tests, simple linear regression tests, T tests and coefficient of determination tests.The results of this research show 1) as many as 45 students (53%) reported that they received a moderate democratic parenting style. 2) There are 13 items on the democratic parenting style scale which are identified as low (not optimal) in communication with parents which is still not two-way, parents' views on children sometimes still do not give children rights and opinions, lack of consistent application of discipline and fair, does not meet psychological needs. 3) A total of 34 students (40%) of the 85 students studied had high (good) social behavior. 4) There were no Low and Very Low item scores on the social behavior scale for generation Z children, 5) There was a contribution from parents' parenting patterns to generation Z's social behavior is 51.4% while 48.6% is influenced by other factors outside the research.